A Systematization of a Research-based Reading Rssessment in Two Middle School Students - Valer Huamán, Isaac (2023)
The main objective of the present study is to systematize an experience of a research-based  reading assessment of two middle school students from a public school in Manhattan, New York during the Fall 2022. In order to select the assessment tests, I asumed the Science of Reading along with the Simple View of Reading perspectives. The tests applied addresed to assess students in three aspects: decoding, fluency, and encoding (spelling). Results showed that, in a nutshell, students are reading below their grade; nevertheless, the fact that they are Colombian inmigrants living one year in the U.S., may explain their results on the assessment tests. In the discussion section, I put into perspective the student’s assessments’ results with their context and personal background in order to have a broader understanding of their reading skills. The implication of this study is to acknowledge the necessity to use research-based assessment  to make the best decision in order to improve student’s reading skills.